Relationship Between Diet and Dental Health In School Going Children of Mixed Dentition Period - Panjiyar, SR; Singh, Samir; Tiwari, K (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Diet and nutrition are significant influencers of oral health, and can affect the development and progression of oral diseases such as caries, periodontal disease, erosion, and others. Sucrose is the most common dietary sugar and is considered the most cariogenic carbohydrate. Frequent consumption of carbohydrates in the form of simple sugars increases the risk of dental caries. The aim of this study was to determine the relationship between diet and dental caries. Methods: The present cross-sectional study was conducted at selected school located in Janakpur sub- metropolitan city over a period of two and half months from 27th February to 10th May, 2024. A total of 400 school going students aged between 6 to below 12 years were included in the study. Semi-structured questionnaire, dental check-up and 24-hour diet recall sheets were used to capture detailed information about all foods consumed by the participants in the past 24 hours, Descriptive analysis and Chi-square tests were presented by using IBM SPSS version 20.0. Results: The mean age of the total population was 9.34±1.47 years. Among 400 participants, 53.5% were male and 46.5% were female. Significant differences in oral hygiene status were found between male and female (p < 0.009). Two hundred forty-five (61.25%) of total students eat 4-5 servings starchy cereals and 81.25% of them reported of eating 1-2 servings of refined carbohydrate products. Dental caries was found in 52.35% in underweight participants and 38.89% in participants with normal BMI. Overall prevalence of dental caries was found to be 50.8% for both permanent and primary tooth. Conclusions: School children of mixed dentition period have higher prevalence of dental caries. Our study revealed that school children of underweight group are more prone to develop dental caries and are associated with low caloric and cariogenic diet. Implementation of proper oral hygiene practice, parental guidance, good food habits and carioprotective diet is recommended to improve dental health in school children.